Development of flipped classroom learning assisted by interactive media on geometry materials for class V elementary school - Syafni Gustina Sari; Yenni Rozimela; Yerizon Yerizon (Universitas Ahmad Dahlan, 2023)
Complaints expressed by teachers currently are that the material is dense and the time given is limited. The teacher's limited time in explaining the material certainly requires students to be able to study independently at home to understand and deepen the material being studied. Teachers cannot control students' understanding of learning material provided through media at home. The aim of this research is to produce effective flipped class learning assisted by interactive media in fifth-grade elementary school class material. This research answers the weakness of flipped classroom learning, namely that teachers cannot control student learning of the material provided through learning media. This type of research involves research and development using 4D models. In this article, what is discussed is the effectiveness of flipped classroom learning assisted by interactive media. Based on the results of the research conducted, it can be concluded that the effectiveness of flipped classroom learning assisted by interactive media is 86.50% in the very effective category. Meanwhile, effectiveness was tested using pre-test and post-test results of 0.73 with a high N-Gain test with effective criteria. From the results of this research, it can be recommended that teachers use flipped classroom learning assisted by interactive media because it has been proven to be effective. Future researchers are advised to conduct research on flipped classes with the help of interactive media and other materials.